Metaphors created by prospective teachers related to the concept of Social Network - Gurol, Mehmet; Donmus, Vildan (Elsevier Science Bv, 2010)
The aim of this study is to determine mental images (metaphors) of prospective teachers related to social networks, playing an important role in daily lives of the individuals from all walks of life most of whom are young. The study group of this research includes prospective teachers from 1st, 2nd, 3rd and 4th grades in Computer Teacher Department of Technical Education Faculty of Firat University in 2009-2010 education year. Data of the study were obtained from the completion of a sentence Social networks are similar to ... ; because ... by prospective teachers. Findings of the study are as follows: prospective teachers created 106 metaphors related to social network. 78 of these metaphors were created by just one student while the rest were created by students ranging from 2 to 11. Male prospective teachers created 76 different metaphors while females created 37. It is seen that the most repeated metaphors were cigarette, tree and chameleon. In addition, metaphors related to the concept of social network created by prospective teachers fall into 7 conceptual categories; rapidly developing and changing, communication, correspondence and sharing, addictive, positive, a negative, both positive and negative, an indispensible platform. (C) 2010 Published by Elsevier Ltd.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: metaphor; social network; mental image